2021
DOI: 10.3389/fneur.2021.649088
|View full text |Cite
|
Sign up to set email alerts
|

Functional Disability After Ischemic Stroke: A Community-Based Cross-Sectional Study in Shanghai, China

Abstract: Objective: This study aimed to understand the demographics, functional disabilities, cognitive impairment, and depressive mood among stroke patients and to explore the correlation between functional disability and the other health conditions so as to provide some data for community rehabilitation among stroke patients.Methods: A cross-sectional study was conducted to investigate the functional status of ischemic stroke patients with stroke history between 1 month and 2 years by applying the modified Rankin Sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…The reported incidence of physical dependence among stroke survivors varies between 15-30% in the USA to 45% in China. 46 We found that old age, previous stroke, AF, and high mRS>2 at discharge were associated with an increased functional disability during the follow-up period.…”
Section: Discussionmentioning
confidence: 64%
“…The reported incidence of physical dependence among stroke survivors varies between 15-30% in the USA to 45% in China. 46 We found that old age, previous stroke, AF, and high mRS>2 at discharge were associated with an increased functional disability during the follow-up period.…”
Section: Discussionmentioning
confidence: 64%
“…Cognitive function was evaluated by experienced neurological physicians using the Chinese version of the Mini-Mental State Examination (MMSE) scale 3 months after lacunar infarction ( 21 ). The MMSE scale was widely used in cognitive function assessment in China ( 22 , 23 ). The total score of MMSE was 30, and the lower scores indicated the worse cognitive function.…”
Section: Methodsmentioning
confidence: 99%
“…Radiologic images were read by a radiologist and were reviewed by an experienced neurologist. (22,23). The total score of MMSE was 30, and the lower scores indicated the worse cognitive function.…”
Section: Lacunar Infarction Definitionmentioning
confidence: 96%
“…The total score is utilized to assess the degree of depression of participants, with scores of ≥5 indicating depression, and scores of 5–9 mild depression; 10–14 moderate depression; 15–19 moderately severe depression; and scores of ≥20 severe depression. This instrument has been validated among various Chinese populations [ 30 , 31 ]. In this study, the Cronbach’s alpha of the instrument was 0.914.…”
Section: Methodsmentioning
confidence: 99%